2012
DOI: 10.1029/2012gl051014
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Rayleigh‐wave tomography of Ireland's crust: Implications for crustal accretion and evolution within the Caledonian Orogen

Abstract: The Irish landmass, now at the western extremity of the Eurasian Plate, was formed in the Caledonian Orogeny during the Palaeozoic assembly of Pangea. The associated closure of the Iapetus Ocean is recorded in the NE–SW structural trends that dominate the tectonic set‐up of Ireland today. The deep‐crustal dynamics of the orogeny and the effect on the crust of the subsequent extension and magmatism in the North Atlantic are debated. Fabrics within deep crustal rocks preserve a record of deformation during and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…The inversions showed that seismic-velocity heterogeneity in the area is relatively weak, which justified our use of a region-average profile to constrain the thermal structure of TdC. Because the lateral variations are relatively small and because the errors of the measurements are larger than in terrestrial studies using the same methods (e.g., Endrun et al, 2011;Pawlak et al, 2012;Polat et al, 2012), the variance reductions given by the tomographic inversions are relatively low (supporting information Figure S1). The maps do show interesting lateral variation in phase velocity; maps for different periods and for stacked period ranges (computed to highlight the dominant anomalies and reduce artifacts) are shown, for completeness, in supporting information Figures S1 and S2.…”
Section: Measurementsmentioning
confidence: 72%
“…The inversions showed that seismic-velocity heterogeneity in the area is relatively weak, which justified our use of a region-average profile to constrain the thermal structure of TdC. Because the lateral variations are relatively small and because the errors of the measurements are larger than in terrestrial studies using the same methods (e.g., Endrun et al, 2011;Pawlak et al, 2012;Polat et al, 2012), the variance reductions given by the tomographic inversions are relatively low (supporting information Figure S1). The maps do show interesting lateral variation in phase velocity; maps for different periods and for stacked period ranges (computed to highlight the dominant anomalies and reduce artifacts) are shown, for completeness, in supporting information Figures S1 and S2.…”
Section: Measurementsmentioning
confidence: 72%
“…The voluminous volcanism in northern Ireland is considered a part of the NAVP (White 1988; White & Lovell 1997; Arrowsmith et al 2005). The low velocities beneath Ireland—the western extremity of Europe—may be related to the opening of the North Atlantic, the Iceland Hotspot activity and episodic Cenozoic magmatism in the region (Rohrman & van der Beek 1996; Wawerzinek et al 2008; O’Donnell et al 2011; Polat et al 2012).…”
Section: Discussion Of the 3‐d Upper‐mantle S‐wave Modelsmentioning
confidence: 99%
“…Anisotropic olivine crystals in the mantle are thought to have only a small 4 signal [Montagner and Nataf , 1986], but the silica-rich nature of the continental crust [e.g., Christensen, 1996] means that it may have different anisotropic properties, rendering both the 2 and 4 anisotropy terms important [e.g., Polat et al, 2012]. Calculations of anisotropy for mineralogical and petrological upper mantle models indicate that Rayleigh waves have weak 4 anisotropy dependence, as opposed to Love waves [Montagner and Nataf , 1986;Montagner and Anderson, 1989].…”
Section: Appendix C: the Importance Of Anisotropymentioning
confidence: 99%
“…Interpreting the 4 anisotropy from a physical point of view is not straightforward: we speculate tentatively that it may be a combination of Rayleigh-Love wave coupling effects or more complex mineralogical anisotropy systems developed locally. We therefore follow the practice of previous studies that calculate both 2 and 4 terms [e.g., Deschamps et al, 2008;Darbyshire and Lebedev, 2009;Fry et al, 2010;Polat et al, 2012] but focus our interpretation solely on the isotropic and the 2 anomalies, in the context of upper mantle structure.…”
Section: Appendix C: the Importance Of Anisotropymentioning
confidence: 99%